ChemInform Abstract: Beyond the Divinyl Ketone: Innovations in the Generation and Nazarov Cyclization of Pentadienyl Cation Intermediates. Issue 40 (12th September 2013) - Spencer, William T. III; Vaidya, Tulaza; Frontier, Alison J.
Abstract Review: 57 refs.